2022
DOI: 10.3390/app12010429
|View full text |Cite
|
Sign up to set email alerts
|

Performance-Enhancing Sulfur-Doped TiO2 Photoanodes for Perovskite Solar Cells

Abstract: High-performance electron transport layer (ETL) anode generally needs to form a uniform dense layer with suitable conduction band position and good electron transport properties. The TiO2 photoanode is primarily applied as the ETL because it is low-cost, has diverse thin-film preparation methods and has good chemical stability. However, pure TiO2 is not an ideal ETL because it lacks several important criteria, such as low conductivity and conduction band mismatch with compositional-tailored perovskite. Thus, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(38 reference statements)
1
3
0
Order By: Relevance
“…The indirect band gap (Eg) of pure TiO 2 and 1 mol% Er-doped TiO 2 was determined to be 3.45 eV and 2.75 eV, respectively, using the Tauc plot (Figure 4 [b]). This kind of decrement in band gap value was also reported by Mutalib et al (18) The considerable reduction in band gap may have been produced by oxygen vacancies brought on by the doping of Er 3+ ions. (19) https://www.indjst.org/ A CIGS solar cell's efficiency is closely correlated with the buffer layer's refractive index.…”
Section: Uv -Visible Spectroscopic Analysissupporting
confidence: 81%
“…The indirect band gap (Eg) of pure TiO 2 and 1 mol% Er-doped TiO 2 was determined to be 3.45 eV and 2.75 eV, respectively, using the Tauc plot (Figure 4 [b]). This kind of decrement in band gap value was also reported by Mutalib et al (18) The considerable reduction in band gap may have been produced by oxygen vacancies brought on by the doping of Er 3+ ions. (19) https://www.indjst.org/ A CIGS solar cell's efficiency is closely correlated with the buffer layer's refractive index.…”
Section: Uv -Visible Spectroscopic Analysissupporting
confidence: 81%
“…The produced S-doped TiO2 showed high absorbance, photocatalytic activity, and photo-current density. This proved that the increase in the electron collection capacity of the carrier charge and photocurrent density enhanced the PCE by 6.0% and showed a better efficiency of 18%, as shown in Table 3 [84]. It showed that the charge transfer resistance (RCT) in the S-doped TiO2 perovskite device was lower than that of the un-doped TiO2 device.…”
Section: Modification Of Tio2 With Metal Dopingmentioning
confidence: 74%
“…Among the various methods used to enhance the bulk properties of TiO2 ETLs, doping with metals ions has received much attention, as it is a simple process that can lead to improved charge transportation ability, elimination of hysteresis, modification of the band structure, modulated electron mobility, and improved thin film conductivity of the ETL with a high charge extraction capacity [76,77]. The numerous metal dopants that have been reported include tin [42,78,79], iron [80], ruthenium [81,82], sulphur [83,84], niobium [85], zinc [86], tantalum [87], and magnesium [77,88].…”
Section: Modification Of Tio2 With Metal Dopingmentioning
confidence: 99%
See 1 more Smart Citation